(untitled) (Journal of EAHIL, 2020)
Reducing environmental harm aims to build a responsible and sustainable future. The University of Eastern Finland (UEF) promotes the United Nations’ (UN) Sustainable Development Goals (SDGs) in all its operations. UEF’s goal is to become carbon neutral by 2025. The Library has staff members in two of the university’s six working groups that chart the carbon emissions of the university and a steering group member.